Proteção dos direitos da comunidade lgbtqqicaapf2k+: adoção por casais homossexuais (cis e/ou trans) sob a luz das leis magna e ordinárias brasileiras - GONÇALVES, Wellerson Rocha Gomes (2024)
This Course Completion Work (CCW) aims to analyze the protection of the rights of LGBTQIAPN+ people in Brazil from the act of adoption, investigating the legislation and the challenges faced by these individuals. The research seeks to understand the main legal guarantees related to the community in question and the adoption process for same-sex couples, as well as their limitations and advances. Being a qualitative research approach, through a bibliographical review and analysis of widely disseminated decisions on the subject, three keywords were identified that reflect the main aspects of this study: protection, adoption and rights. The keyword "protection" encompasses the need to create public policies that ensure the protection of LGBTQIAPN+ rights, in order to combat discrimination and violence based on sexual orientation and gender identity. The keyword "adoption" highlights the relevance of the topic and the importance of guaranteeing the right of same-sex couples to adopt children, regardless of their sexual orientation. The State's responsibility to ensure that children and adolescents are adopted in welcoming environments free from prejudice is also highlighted. Finally, the keyword "rights" refers to the discussion about the recognition of the civil rights of LGBTQIAPN+ people, including the right to adoption. It also discusses the history of achievements and challenges faced by the LGBTQIAPN+ community so that their rights are respected and guaranteed in the Brazilian context. It is concluded that, although there are significant advances in Brazilian legislation, there are still challenges to be overcome with regard to protecting the rights of LGBTQIAPN+ people in the context of adoption. To achieve this, it is necessary to promote awareness, dialogue and strengthening public policies that guarantee equality and inclusion of this population, ensuring the full exercise of their rights.